Numerical Study of Stability of Retaining Walls in the Presence of Horizontal and Chimney Drainage - Salmasi, Farzin; Abraham, John; Bakhshayesh, Behrouz Oghati (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
With heavy rainfall, underground water levels and pore water pressures can increase and cause earthen slope failure. Retaining walls are common structures that are used to increase earthen slope stability. In the present study, the stability of earthen slopes in critical hydrological cases was numerically simulated; the simulations included pore pressure behind the retaining walls, which led to instability. Among the investigated parameters were precipitation intensity, soil type, position, and the diameter of the drainage passages. Both horizontal and chimney drainages were used. In this study, the performance of horizontal and chimney drains in controlling pore water pressure and the stability of soil slopes during heavy rains are studied using two software programs, SEEP/W and SLOPE/W. First, the desired soil slope was modeled using SEEP/W software, and then, by defining the available materials and boundary conditions, the pore water pressure was determined. The results are then entered into the SLOPE/W software, and the effect of using horizontal and chimney drains on slope stability during heavy rainfall is investigated. Transient flow conditions are created with three soil textures located behind of retaining wall. The total number of simulated models was 150 cases, which comprised five cases for different distances of the horizontal drain from the retaining wall invert (h), five thicknesses of the chimney drain (T), two precipitation intensities (P), and three instances for soil texture. In an unsaturated medium, the soil characteristic curve, i.e., a relation between soil moisture and soil suction, is needed. Results show that for fine-grained soils with intensive precipitation, a single horizontal drainage passageway was unable to provide sufficient stability for the retaining wall. A retaining wall provides stability for coarse-grained soils with a single horizontal drainage pipe; the horizontal pipe can discharge the excess water behind the retaining wall. A chimney drainage system provides the best results and the stability of the retaining wall did not face any danger, even under the most severe circumstances. Concerning overturning moment and water pore pressure behind the wall, linear and non-linear regression relations are produced in dimensionless form. The accuracy of the regression relations supported their use in practical applications.